Munasabah Al-Qur'an as a Method of Transforming Islamic Education Values - Zumratul Azka; Hafidz Yuliansyah; Dwi Ratnasari (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2026)
The concept of munasabah offers a holistic approach to understanding the values contained in Islamic education. The aim of this research is to analyze the conception of the munasabah of the Qur'an as a method of transforming the values of Islamic education using library methods. The results of the research show that the munasabah of the Qur'an is a strategic approach in transforming the values of Islamic education which are always relevant to the times. Through the relationship between verses, the concepts of monotheism, morals and worship can be systematically integrated into the Islamic education curriculum. This approach educates students not only intellectually, but also with strong Islamic character, so that they are able to implement the values contained in the Qur’an in their daily lives. Thus, the munasabah of the Qur'an makes Islamic education more holistic and applicable in forming a generation that has faith, has noble character, and contributes to society